2023
DOI: 10.1002/lno.12412
|View full text |Cite
|
Sign up to set email alerts
|

The physiological response of an Antarctic key phytoplankton species to low iron and manganese concentrations

Abstract: Iron (Fe) and manganese (Mn) availability and the divergent requirements of phytoplankton species were recently shown to be potential important drivers of Southern Ocean community composition. Knowledge about Antarctic phytoplankton species requirements for Fe and Mn remains, however, scarce. By performing laboratory experiments and additional calculations of the photosynthetic electron transport, we investigated the response of the ecologically important species Phaeocystis antarctica under a combination of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…A consequence is the well-known limitation of Southern Ocean productivity by Fe (Martin et al, 1990;Moore et al, 2013), demonstrated in situ by Fe enrichment experiments carried out around the turn of the millennium (e.g., Boyd et al, 2000;Gervais et al, 2002;Coale et al, 2004). More recently, evidence has emerged that the low Mn concentrations of the surface Southern Ocean can also lead to (co-)limitation of productivity by Mn (Wu et al, 2019;Pausch et al, 2019;Browning et al, 2021;Latour et al, 2021;Balaguer et al, 2022Balaguer et al, , 2023.…”
Section: Box 1 Iron and Manganesementioning
confidence: 99%
“…A consequence is the well-known limitation of Southern Ocean productivity by Fe (Martin et al, 1990;Moore et al, 2013), demonstrated in situ by Fe enrichment experiments carried out around the turn of the millennium (e.g., Boyd et al, 2000;Gervais et al, 2002;Coale et al, 2004). More recently, evidence has emerged that the low Mn concentrations of the surface Southern Ocean can also lead to (co-)limitation of productivity by Mn (Wu et al, 2019;Pausch et al, 2019;Browning et al, 2021;Latour et al, 2021;Balaguer et al, 2022Balaguer et al, , 2023.…”
Section: Box 1 Iron and Manganesementioning
confidence: 99%